Early Experience With Eravacycline for Complicated Infections. (2nd March 2020) - Alosaimy, Sara; Molina, Kyle C; Claeys, Kimberly C; Andrade, Justin; Truong, James; King, Madeline A; Pullinger, Benjamin M; Huang, Glen; Morrisette, Taylor; Lagnf, Abdalhamid M; Davis, Susan L; Rybak, Michael J
Abstract: Eravacycline (ERV) was used in 35 patients for various infections. The most common pathogen was Klebsiella pneumoniae, and 30-day survival was 74%. Absence of 30-day recurrence and resolution of signs and symptoms of infection were 91% and 57%, respectively. ERV was well-tolerated, with adverse events leading to drug discontinuation in one patient.